Novel Design of polycrystalline CdTe/Si Tandem Solar Cells Using SiO2/TiO2 Distributed Bragg Reﬂector - Rouhbakhshmeghrazi, Amirreza; Madadi, Mahdi (TECCIENCIA, 2020)
In this paper, a polycrystalline cadmium telluride/silicon (C dT e/Si) solar cell based on SiO /T iO 2 2 distributed Bragg reﬂector (DBR) is proposed and investigated using calibrated simulations with experimental data of previous fabrication device. At ﬁrst, by inserting the SiO /T iO 2 2 DBR, the conversion eﬃciency is increased by about 25% compared with the conventional C dT e/Si solar cell with similar dimen- sions. In addition, the carrier lifetime of absorber layer can provide an improved conversion eﬃciency of 15% compared with the C dT e/Si conventional solar cell. The obtained open circuit voltage, short circuit current density, ﬁll factor and con- version eﬃciency of proposed solar cell structure were about 1.2V, 39.5mA/cm , 0.95 and 28.5% under global AM 1.5 conditions, respectively. The results strongly con-2 ﬁrm that the polycrystalline C dT e/Si solar cell based on SiO /T iO2 2 DBR seems to be the most optimal choice for converting the solar energy in high eﬃciency photovoltaics systems.